Avaliação da prevalência e fatores de risco a cárie dentária em crianças na faixa etária de 6 a 9 anos que receberam atenção odontológica na primeira infância - Martins, Vanessa Roma (2007)
The objective of this research was to evaluate the prevalence and risk factors for dental caries in children aged 6 to 9 years who receive dental care in early childhood through the Baby Clinic UNIGRANRIO, and check its correlation with the identified rich factors . The sample consists of 184 children, 88 (47.8%) female and 96 (52.2%) were male, aged 6 (91-49%), 7 (36-20%), 8 (37-20%) and 9 (20-11%) years. The prevalence of caries was 21.2% (39) in total and 61.5% (24) and 38.5% (15) for females and males respectively, showing no statistically significant difference (p = 0 , 08). The average DMFT was 0.6 ± 1.3, and 0.6 ± 1.1 for females and 0.5 ± 1.5 for males. Among the risk factors studied were those related to caries are oral hygiene habits (p = 0.01 - to 7 years old), the pattern of sugar consumption (p = 0.02), nutritional habit breastfeeding chest (p = 0.04). And the factors that are unrelated to the presence of carious lesions are criaça sex and age (p = 0.2 to 6 years / p = 0.7 to 8 years / p = 0.5 to 9 years), the presence visible biofilm (p = 0.85), parents' level of formal education (p = 0.33 - parents / p = 0.87 - mothers) and presence of nourishing the bottle habit (p = 0.08).